The possibility of applying calculation based on queuing theory with the aim of real-time control - V. I. Kudriavtsev; О. F. Zirko (Системный анализ и прикладная информатика)
Possibilities of using mathematical models of the theory of queues for the purpose of control of processes of discrete productions modeled by it in real time are investigated. As a model example, a system for managing the rearrangements of service items in queues was considered. For the analysis the methods of calculation of BMAP-controlled systems and the methods of the theory of recovery on periods of employment for queues with vacancies of requirements were used.As a result of research it is found out that mathematical modeling in the theory of queues can be used for simulation of discrete production for the purpose of design and the production analysis, but cannot be used for management of the modeled processes in real time.